Seismites in the Kathmandu basin, Nepal - Gajurel, A. P.; Huyghe, P.; Lanord, C. France-; Mugnier, J. L.; Upreti, B. N.; Fort, P. Le (Journal of Nepal Geological Society, 1998)
The Kathmandu valley is a large intermontane basin carried above the Himalayan major decollement. It is limited southward by the Mahabharat Range, which forms the hanging wall of the Mahabharat Thrust, and northward by the Shivapuri Range. The Kathmandu basin is filled with a very thick (500-600 m) sequence of fluvio-lacustrine Plio-Pleistocene sediments, which unconformably overlie the folded and faulted Precambrian-Palaeozoic Kathmandu Complex. These semi-consolidated deposits mainly consist of fine to coarse sand, sandy loam, sandy silty clay, and gravely conglomerate. New field data show that small-scale deformational structures occur in the lacustrine deposits of the central and southern parts of the Kathmandu basin. In Thimi section, these structures take place within sub horizontal clayey layers. They mainly consist of finely contorted and folded sandy layers which form balls and pillows of about 10-13cm thick. In a few places, the deformational structures are associated with small folds and micro-faults (normal and reverse faults), with micro-breccias and sand dykes. The convolute lamination structures show no preferential verging, thus, excluding shearing related to the influence of a palaeoslope. Such structures have been found in three different places and they were always confined to single stratigraphic horizons positioned between undisturbed parallel beds. The deformational structures described above show characteristics of seismites. The associated seismic events may be related to major earthquakes or movements along the active nearby faults. Earthquake-induced liquefaction and subtle variations in physiomechanical properties of water-saturated fine sandy sediments have probably controlled the deformational pattern.